HUBUNGAN ANTARA KONSEP DIRI DENGAN PERILAKU ASERTIF SISWA KELAS XI - Astuti, Dwi Wahyu; Muslikah, Muslikah (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
Low assertive behavior of students is shown by the inhibition of the process of socialization, such as having the belief that he can not overcome the problem, unable to defend personal rights and neglect of the rights of others, and individuals are not able to consider decisions well. This study aims to analyze the existence of a significant and positive relationship between self-concept and assertive behavior of students. This kind of research used correlational design with a total of 174 students for a sample that taken using Simple Random Sampling Technique, and for collecting the datas we used the scale of self-concept and the scale of assertive behavior that will be analyzed by using correlation method. Coefficient correlation obtained result (R=0.310) in the low category and significant value (P=0.000) so So if students have positive self-concepts, students' assertive behavior will also be high. Implications for guidance and counseling teachers need to provide group or classical services that contain that every individual is expected to have assertive behavior or with training to improve assertive behavior. The ability of assertive behavior is also accompanied by having the ability to have a positive self-concept.